1979
DOI: 10.1016/0092-8674(79)90237-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of yeast histone genes H2A and H2B

Abstract: Analysis of cloned sequences for yeast histone genes H2A and H2B reveals that there are only two copies of this pair of genes within the haploid yeast genome. Within each copy, the genes for H2A and H2B are separated by approximately 700 bp of spacer DNA. The two copies are separated from one another in the yeast genome by a minimum distance of 35-60 kb. Sequence homology between the two copies is restricted to the genes for H2A and H2B; the spacer DNA between the genes is nonhomologous. In both copies, the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
143
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(148 citation statements)
references
References 22 publications
4
143
0
1
Order By: Relevance
“…Total genomic DNA was prepared from S. pombe spheroplasts (Hereford et al 1979). DNA was restricted, fractionated on a 0.8% agarose gel and then transferred on to a nylon membrane (Biodyne A, Nihon Pall Co., Tokyo).…”
Section: Southern and Northern Blottingmentioning
confidence: 99%
“…Total genomic DNA was prepared from S. pombe spheroplasts (Hereford et al 1979). DNA was restricted, fractionated on a 0.8% agarose gel and then transferred on to a nylon membrane (Biodyne A, Nihon Pall Co., Tokyo).…”
Section: Southern and Northern Blottingmentioning
confidence: 99%
“…Neither of these gene pairs is essential, but the cell requires one HHT-HHF locus for survival, indicating that H3 and H4 are essential (Smith and Stirling 1988). The other two loci, HTA1-HTB1 and HTA2-HTB2, encode almost identical H2A and H2B proteins (Hereford et al 1979). Initially, it was thought that HTA1-HTB1 and HTA2-HTB2 could also substitute for one another, although it was clear that HTA1-HTB1 is not equivalent to HTA2-HTB2 because deletion of the former is associated with a significant growth phenotype, whereas deletion of the latter has no obvious effect (Norris and Osley 1987).…”
mentioning
confidence: 99%
“…Several different yeast genes conferring resistance to antibiotic inhibitors of translation, at least one of which has been proven to be a ribosomal protein gene (32), are not linked to each other (32)(33)(34)(35). In fact, genetic mapping and recombinant DNA studies have revealed only three clusters of related yeast genes coding for separate polypeptides: the gal 1, 7, 10 cluster (36), the histone genes H2A and H2B (37), and the dal 1, 4, 2 cluster (38).…”
Section: Discussionmentioning
confidence: 99%